Modified approach for harmonic reduction in three-phase to seven-phase using transformer winding connections - Mehrdad Ahmadi Kamarposhti; Ashkan Abyar Hosseini (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Three phase supply is available in the generating station or grid, were as seven phase supply is required for many industrial applications such as, aerospace, railway and automobile applications. There are different methods in which we can convert 3 to 7 phase using 24-Pulse Converter, Carrier Based PWM Technique, multilevel converter and Multiphase Transformer. The above said methods which are more complicated to design for higher ratings or a pure sine wave will not be obtained or harmonics will be more. For Multiphase power transmission system multiphase transformers are needed. In the multiphase power transmission and multiphase rectifier systems, the number of phase can be designed and developed in multiples of three. Therefore, the variable speed multiphase drive system considered in the literature are mostly of five, seven, nine, eleven, twelve, and fifteen phase. So, there is a need to design and develop special transformer which converts from 3 to 7 phase for different arrangement of input and output. Thus, with the proposed technique, a pure seven-phase sine-wave of fixed voltage/current and frequency is obtained, which can be used for RL load and motor testing purposes. Complete design and simulation of the proposed solution is presented. Analytical calculation and simulation results for RL load is presented in the paper. This model can be simulated by using Orcad simulation software and “SimPowerSystem” block sets of MATLAB/SIMULINK software.